P078 Predicting initial AutoPAP pressures in children - how do we perform ?. (9th November 2022) - Mihai, R; Nisbet, L; Ellis, K; Davey, M; Nixon, G
Abstract: Introduction: Auto-titrating positive airway pressure (APAP) with remote monitoring provides valuable information on pressure requirements during acclimatisation to APAP in children. However there are no reliable predictors of pressure requirements in children to help guide clinician prescribing upon commencement of APAP. Methods: Retrospective review of children commencing outpatient APAP in tertiary hospital from 2017-2022. Initial APAP prescription was at treating physician discretion and changes over subsequent days were based on review of remote monitoring data. Results: 111 children commenced APAP (86 male; median 13.7y; range 3.7-19.3y). Initial minimum APAP pressure ranged from 4-6cmH2O (median 4cmH2O), and maximum pressure ranged from 6-16cmH2O (median 12cmH2O). 69 (62%) required no pressure changes; 42 (38%) required 1 or more changes. Children who required ≥1 change had a lower initial maximum pressure than those not requiring change (median 10cmH2O versus 12cmH2O, p<0.01) and were younger (median 9.6y versus 14.8y, p<0.01). There was no significant difference between the two groups for minimum initial pressure, OAHI on diagnostic PSG or BMI z-score. Median days from initiation to the first change was 4d (IQR 2, 11). Pressure adjustments were typically conservative increases in APAP maximum (median +2cmH2O; range -4 to +5cmH2O). The main indication for change was remote monitoring data showing pressures frequently approaching APAP maximum pressure. Discussion: This study shows that clinicians are more likely to under-prescribe initial maximum APAP pressure in young patients, leading to a higher number of adjustments required to reach satisfactory therapy. Further investigations will assess the impact of prescription changes on adherence.